How death anxiety influences coping strategies during the COVID-19 pandemic: investigating the role of spirituality, national identity, lockdown and trust. Issue 17 (22nd November 2021) - Partouche-Sebban, Judith; Rezaee Vessal, Saeedeh; Sorio, Rossella; Castellano, Sylvaine; Khelladi, Insaf; Orhan, Mehmet A.
ABSTRACT: The COVID-19 pandemic has created a highly stressful environment in which reminders of death are constant. This context of permanent mortality salience is likely to arouse death anxiety in individuals around the world that they must manage. This study investigates the effects of death anxiety on the adoption of different coping strategies during the COVID-19 pandemic in five different countries (N = 721, mean age = 32.83). The results show that higher levels of death anxiety mainly lead to the adoption of avoidance coping strategies and that spirituality and national identity moderate this effect, whereas lockdown does not. Moreover, trust in institutions is a mediator in the relationship between death anxiety and avoidance strategies.